Impacts of COVID-19 on Food Security: Panel Data Evidence from Nigeria - Mulubrhan Amare; Kibrom A. Abay; Luca Tiberti; Jordan Chamberlin (Global Labor Organization (GLO), 2020)
This paper combines pre-pandemic face-to-face survey data with follow up phone surveys collected in April-May 2020 to quantify the overall and differential impacts of COVID-19 on household food security, labor market participation and local food prices in Nigeria. We exploit spatial variation in exposure to COVID-19 related infections and lockdown measures along with temporal differences in our outcomes of interest using a difference-in-difference approach. We find that those households exposed to higher COVID-19 cases or mobility lockdowns experience a significant increase in measures of food insecurity. Examining possible transmission channels for this effect, we find that COVID-19 significantly reduces labor market participation and increases food prices. We find that impacts differ by economic activities and households. For instance, lockdown measures increased households' experience of food insecurity by 13 percentage points and reduced the probability of participation in non-farm business activities by 11 percentage points. These lockdown measures have smaller impacts on wage-related activities and farming activities. In terms of food security, households relying on non-farm businesses, poorer households, those with school-aged children, and those living in remote and conflicted-affected zones have experienced relatively larger deteriorations in food security. These findings can help inform immediate and medium-term policy responses, including social protection policies aiming at ameliorating the impacts of the pandemic, as well as guide targeting strategies of governments and international donor agencies by identifying the most impacted sub-populations.
Keywords: I12; O13; Q18; Q12; Q18; 330; COVID-19; Pandemic; Food security; labor market participation; food price